Pengaruh Aricula Acupressure Terhadap Tingkat Depresi pada Pasien Stroke: The Effect of Auricular Acupressure on Depression Levels in Stroke Patients - Purnama, Agus; Susaldi (MPI Press, 2023)
Introduction: Stroke is one of the leading global health problems and is often a complication of various degenerative diseases such as hypertension and diabetes. The prevalence of stroke as a degenerative condition has reached approximately 104.2 million people worldwide over the past three years. Objectives: This study aimed to evaluate the effectiveness of auricular acupressure in reducing depression among stroke patients. Methods: A randomized controlled trial design was used involving 24 respondents. Depression levels were measured before and after the intervention. Result: The findings revealed that the mean depression score before the intervention was 63.9 (SD =8.76), which significantly decreased to 50.6 (SD = 9.47) after the intervention. The effect size analysis yielded a value of -3.97, indicating a substantial effect of the intervention. Moreover, the p-value of 0.000 confirmed the statistical significance of this reduction. Conclusion: These findings support the hypothesis that auricular acupressure is effective in reducing depression levels among stroke patients. However, the study is limited by its small sample size and single-site setting, which may affect the generalizability of the results. Further studies with larger and more diverse populations are recommended.